Robust abdominal imaging with incomplete breath‐holds. Issue 5 (1st July 2013) - Gdaniec, Nadine; Eggers, Holger; Börnert, Peter; Doneva, Mariya; Mertins, Alfred
Abstract Purpose Breath‐holding is an established strategy for reducing motion artifacts in abdominal imaging. However, the breath‐holding capabilities of patients are often overstrained by scans with large coverage and high resolution. In this work, a new strategy for coping with resulting incomplete breath‐holds in abdominal imaging is suggested. Methods A sampling pattern is designed to support image reconstruction from undersampled data acquired up to any point in time using compressed sensing and parallel imaging. In combination with a navigator‐based detection of the onset of respiration, it allows scan termination and thus reconstruction only from consistent data, which suppresses motion artifacts. The spatial resolution is restricted by a lower bound of the sampling density and is increased over the scan, to strike a compromise with the signal‐to‐noise ratio and undersampling artifacts for any breath‐hold duration. Results The sampling pattern is optimized in phantom experiments and is successfully applied in abdominal gradient‐echo imaging including water‐fat separation on volunteers. Conclusions The new strategy provides images in which motion artifacts are minimized independent of the breath‐holding capabilities of patients, and which enhance in terms of spatial resolution, signal‐to‐noise ratio, and undersampling artifacts with the a priori unknown breath‐hold duration actually achieved in a particular scan. Magn Reson Med 71:1733–1742, 2014. © 2013 Wiley Periodicals, Inc.